Polysaccharide-rich extract of Potentilla anserina ameliorates nonalcoholic fatty liver disease in free fatty acid-induced HepG2 cells and high-fat/sugar diet-fed mice - Xiujun Lin; Yimei Zheng; Yingying Yan; Hongting Deng; Shunxin Wang; Yuanju He; Yuting Tian; Wenhui Zhang; Hui Teng (Food Science and Human Wellness)
Potentilla anserina L. (PA) belongs to the Rosaceae family, is a common edible plant in the Qinghai-Tibet Plateau areas of China. This study elucidates the mechanism upon which crude polysaccharide of PA (PAP) on fat accumulation in HepG2 cells stimulated by oleic acid (OA) and high fat high sugar induced mice. The result revealed that PAP inhibited lipid accumulation in obese mice and ameliorated the degree of damage in OA-induced HepG2 cells. Specifically, compared to the control group, the TG and TC levels were decreased in cells and mice serum, the aspartate transaminase and alamine aminotransferase contents were declined in liver of obese mice by PAP treatment. The expressions of adipogenic genes of SREBP-1c, C/EBPα, PPARγ, and FAS were inhibited after PAP treatment. Moreover, PAP increased the mRNA levels of CPT-1 and PPARα, which were involved in fatty acid oxidation. The present results indicated the PAP could alleviate the damage of liver associated with obesity and PAP treatment might provide a dietary therapeutic option for the treatment of hyperlipidemia.